Effect of Complex Training on Aerobic and Anaerobic Power of Amateur Athletes - Kumar, Gopal; Pandey, Vivek (Physical Education Theory and Methodology, 2023)
The study purpose was to investigate the effect of complex training on aerobic and anaerobic power of amateur athletes. Materials and methods. The study included 30 amateur athletes in soccer and hockey, which were equally divided into two groups, namely an Experimental group who underwent 6 weeks of complex training along with regular training in their sports and a Control Group who only performed their regular sports training. Anaerobic power was assessed by Running-based Anaerobic Sprint Test (RAST) and aerobic power (VO₂max) was assessed by 12-min Cooper run/walk test. The study used the Pre-test Post-test Randomized Group Design, and Paired t-test was used as the statistical technique for data analysis at a significance level of 0.05. Results. At the end of six weeks, the Experimental group showed significant improvement in anaerobic power and VO₂max, while only VO₂max was improved in the Control group (p<0.05). No significant improvement was observed in anaerobic power for the Control group (p>0.06). Therefore, this shows that complex training has significant effect on anaerobic power, while it does not produce significant improvements in aerobic power. Conclusions. Six weeks of complex training integrated with regular sports training can improve anaerobic power. Coaches and athletes, specifically in soccer and hockey, can implement the complex training program in their regular training.